Identification of vector-borne pathogens in dogs and cats from Southern Brazil - Malheiros, J.; Costa, M. M.; do Amaral, R. B. [UNESP]; de Sousa, K. C.M. [UNESP]; André, M. R. [UNESP]; Machado, R. Z. [UNESP]; Vieira, M. I.B. (Elsevier, 2016)
Dogs and cats are often infected with vector-borne pathogens and play a crucial role as reservoirs and hosts in their life cycles. The aim of the present study was to investigate the occurrence of vector-borne pathogens among dogs and cats in the northwestern region of Rio Grande do Sul (RS) State, Brazil. One hundred and ten blood samples were collected from dogs (n = 80) and cats (n = 30). Laboratory analysis were carried out through stained blood smears, indirect enzyme-linked immunosorbent assay (ELISA) for Babesia vogeli and Ehrlichia canis (only for dogs) and polymerase chain reaction (PCR) aiming the detection of pathogens. The following pathogens were screened by PCR among dogs and cats: Babesia spp. and Hepatozoon spp. (18S rRNA gene), Anaplasma spp. (16S rRNA gene), and Ehrlichia spp. (dsb gene for dogs and 16S rRNA gene for cats) and Bartonella spp. (nuoG gene only for cats). Using blood smears structures morphologically compatible with piroplasms were found in 5.45% (6/110) of the samples. Anti-B. vogeli and anti-E. canis antibodies were detected in 91% (73/80) and 9% (7/80) of the dogs, respectively. All the seropositive dogs to E. canis were also to B. vogeli. Nineteen (17.3%) animals were positive to hemoparasites by PCR. After sequencing Rangelia vitalii 6/80 (7.5%), B. vogeli 3/80 (4%), Hepatozoon spp. 1/80 (1%), and Anaplasma spp. 1/80 (1%) were found in the dogs, and B. vogeli 2/30 (7%) and Bartonella spp. 6/30 (20%) were detected in the screened cats. No sample was positive for genes dsb and 16S rRNA of Ehrlichia spp. Only those animals which were positive for R. vitalii showed findings compatible with rangeliosis, such as anemia (100%), thrombocytopenia (67%), jaundice (50%), external bleeding (50%), and anorexia (50%). This is the first time that B. vogeli detected among cats in Southern Brazil.
Keywords: Brazil; Cats; Dogs; PCR; Ticks; VBD